RISK FACTORS OF PREMATURE RUPTURE OF MEMBRANES IN AYUB TEACHING HOSPITAL: A CASE CONTROL STUDY - Toqueer, Mahwish; Javaid, Mahnoor; Nazneen, Zainab; Ahmed, Khalid; Hayauddin, Hizbar; Toqueer, Umair (Pakistan Journal of Physiology, 2022)
Background: Premature rupture of membranes (PROM) is one of the important causes of preterm delivery and is associated with increased incidence of neonatal and maternal morbidity and mortality worldwide. The aim of this study was to find out the risk factors associated with PROM in patients admitted to Obstetrics Ward of Ayub Teaching Hospital, Abbottabad. Methods: This case control study was conducted on pregnant females (>28 weeks gestation) from 1st November, 2018 to 30th May, 2019. The sample size was 195 patients (130 controls, 65 cases in 2:1 ratio) collected through convenient sampling. Data was analysed using SPSS-16. Odds ratio with confidence interval was used to estimate the strength of association of PROM with its risk factors, and p?0.05 was considered significant. Results: The mean age of the patients was 25.48±3.65 years ranging between 19–38 years. Most of the patients belonged to the age group 26–35 years. Most women were illiterate, unemployed, and had poor socio-economic background. The most important risk factors of PROM were PROM in previous pregnancies (OR=3.978, CI=1.484–10.666, p=0.012), foul smelling vaginal discharge (OR=2.700, CI=1.197–6.089, p=0.014), polyhydramnios (OR=2.5, CI=1.178–5.404, p=0.015), and vaginal bleeding (OR=2.486, CI=1.117–5.534, p=0.023). Conclusion: PROM in previous pregnancies, foul smelling vaginal discharge, vaginal bleeding, and polyhydramnios were found to increase the risk of PROM significantly. Pak J Physiol 2022;18(1):44–7